Assessment of Resident Knowledge in Pediatric Rheumatology. (December 2021) - Guglielmo-Roxby, Tiffany; Louissaint, Valerie; Ettinger, Abigail; Llanos, Adana; Cahill, Ellen; Chefitz, Dalya; Boneparth, Alexis; Amato, Indira; Moorthy, Lakshmi Nandini
Pediatric Rheumatic illnesses are complex, chronic, and often multi-systemic. Our goal was to assess the efficacy of 2 standardized pediatric rheumatology lectures, administered to pediatric residents, in improving the pediatric residents' knowledge and confidence in pediatric rheumatology. Two lectures, 1 hour each, were delivered by 2 residents and given 1 week apart to 28 pediatric residents. Pre- and post-tests assessed knowledge and residents' self-rated competence. Change in knowledge was assessed using paired t -tests. Twenty-eight residents participated in the study. Sixty-three percent (17/27) had an improvement in score from pre-test to post-test. Thirty-seven percent (10/27) reported increased competence from pre-test to post-test. Ninety-six percent (22/23) of the residents found the lectures to be beneficial. Residents in the third post-graduate year (PGY3) cohort had the most significant improvement in scores. The lectures given to the pediatric residents increased pediatric knowledge and the pediatric residents found these lectures to be beneficial.